Loyalitas Konsumen : Konseptualisasi, Anteseden dan Konsekuensi - Sri Rahayu; Mugi Harsono (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
Customer loyalty has been recognized as a dominant factor in the success of business organizations. It has therefore received a great deal of attention in marketing and management theory and practice. This article aims to explain the important role of customer loyalty variables in marketing activities. In addition to explaining the determinants or antecedents of customer loyalty. In addition, this research will also identify the consequences that arise from consumer loyalty, which has an impact on managerial policies that are useful for the company.